Memaknai Tanggung Jawab Renteng Dalam perusahaan Terhadap Tindak Pidana Perpajakan - Dharmasetya, Lani; Gunadi, Ariawan (Jurnal Suara Hukum, 2023)
The articles in the Tax Crime Act are legal affairs, which can be defined as tax- related criminal deed related to accountability of the aforementioned deed both as individual taxpayers and corporate taxpayers. This is further elucidated in the Circular Letter of Supreme Court (SEMA) no. 4 year 2021 regarding Corporate Responsibility in the Field of Taxation, which stipulate that every individual is defined as an individual and a corporation and efforts to resolve tax crimes. Tax crimes are further elucidated in Articles 38, 39, 39A, 40, 41, 41A, 41B, 41C, 43 and Article 43A. In those articles, it is described that the types of tax crimes in the form of negligent or (culpa) is deeds categorized as both unintentional and intentional or criminal (dolus).